Alteration of Sarcoplasmic Reticulum Ca2+ Release in Skeletal Muscle from Calpain 3-Deficient Mice. (12th January 2009) - Dayanithi, Govindan; Richard, Isabelle; Viero, Cédric; Mazuc, Elsa; Mallie, Sylvie; Valmier, Jean; Bourg, Nathalie; Herasse, Muriel; Marty, Isabelle; Lefranc, Gérard; Mangeat, Paul; Baghdiguian, Stephen
Abstract : Mutations ofCa 2 + -activated proteases (calpains) cause muscular dystrophies. Nevertheless, the specific role of calpains inCa 2 + signalling during the onset of dystrophies remains unclear. We investigatedCa 2 + handling in skeletal cells from calpain 3-deficient mice.[ Ca 2 + ] i responses to caffeine, a ryanodine receptor (RyR) agonist, were decreased in −/− myotubes and absent in −/− myoblasts. The −/− myotubes displayed smaller amplitudes of theCa 2 + transients induced by cyclopiazonic acid in comparison to wild type cells. Inhibition of L-typeCa 2 + channels (LCC) suppressed the caffeine-induced[ Ca 2 + ] i responses in −/− myotubes. Hence, the absence of calpain 3 modifies the sarcoplasmic reticulum (SR)Ca 2 + release, by a decrease of the SR content, an impairment of RyR signalling, and an increase of LCC activity. We propose that calpain 3-dependent proteolysis plays a role in activating support proteins of intracellularCa 2 + signalling at a stage of cellular differentiation which is crucial for skeletal muscle regeneration.